Identification of Six Novel Variants of ACAD8 in Isobutyryl-CoA Dehydrogenase Deficiency With Increased C4 Carnitine Using Tandem Mass Spectrometry and NGS Sequencing - Zhuang, Dan-Yan; Ding, Shu-Xia; Wang, Fei; Yang, Xiang-Chun; Pan, Xiao-Li; Bao, You-Wei; Zhou, Li-ming; Li, Hai-bo (Frontiers in Genetics, 2022)
Abstract Isobutyryl-CoA dehydrogenase deficiency (IBDHD, MIM: #611283) is a rare autosomal recessive hereditary disease, which is caused by genetic mutations of acyl-CoA dehydrogenase (ACAD) 8 and associated with valine catabolism. Here, tandem mass spectrometry (MS/MS) was applied to screen 302,993 neonates for inherited metabolic diseases (IMD) in Ningbo of China from 2017 to 2020. The results suggest that 198 newborns (0.7‰) were initially screened positive for IBDHD with C4-Carnitine, and 27 cases (0.1‰) were re-screened positive. Genetic diagnosis was performed on 21 of the 27 cases. Seven compound heterozygous variations, three biallelic variations,and one heterozygous variation of ACAD8 were found with a pathogenicity rate of 33.3%（7/21）. In addition, seven biallelic variations, one heterozygous variation of acyl-CoA dehydrogenase short chain (ACADS), and one biallelic variation of acyl-CoA dehydrogenase short/branched chain (ACADSB) was detected. Further research showed that ACAD8 mutations of 11 IBDHD cases distributed in six different exons with total 14 mutation sites. Seven of which were known suspected pathogenic sites (c.286G>A, c.553C>T, c.1000C>T, c.409G>A, c.500del) and seven were novel mutation sites: c.911A>T, c.904C>T, c.826G >A, c.995T>C, c.1166G>A, c.553C>T, c.1165C>T. This finding enriched the mutation spectrum of ACAD8 in IBDHD.